1α-Hydroxy derivatives of 7-dehydrocholesterol are selective liver X receptor modulators. Issue 172 (September 2017) - Endo-Umeda, Kaori; Aoyama, Atsushi; Shimizu, Masato; Ishikawa, Minoru; Hashimoto, Yuichi; Yamada, Sachiko; Makishima, Makoto
Highlights: 1α-Hydroxy derivatives of 7-dehydrocholesterol (7-DHC) activate liver X receptors. 1, 25-(OH)2 -7-DHC induces unique cofactor peptide association. 1, 25-(OH)2 -7-DHC suppresses proinflammatory gene expression in macrophages. 1, 25-(OH)2 -7-DHC interacts with liver X receptor α differently from potent agonists. Abstract: The nuclear receptors liver X receptor (LXR) α and LXRβ are involved in the regulation of lipid metabolism, inflammation, immunity, cellular proliferation, and apoptosis. Oxysterols are endogenous LXR ligands, and also interact with other nuclear and membrane receptors. We previously reported that a phytosterol derivative with a 1α-hydroxy group acts as a potent LXR agonist with intestine-selective action and that 25-hydroxy and 26/27-hydroxy metabolites of 7-dehydrocholesterol (7-DHC) exhibit partial LXR agonism. In this study, we report that 1α-hydroxy derivatives of 7-DHC, 1α-OH-7-DHC and 1, 25-(OH)2 -7-DHC, act as LXR modulators. Luciferase reporter gene assays showed that 1α-OH-7-DHC activates LXRα and LXRβ and that 1, 25-(OH)2 -7-DHC activates both LXRs and vitamin D receptor. Examination of cofactor peptide association showed that the 1α-hydroxy derivatives, specifically 1, 25-(OH)2 -7-DHC, induce association of coactivator/corepressor peptide in a different manner from the agonist T0901317. Docking modeling and alanine mutational analysis of LXRα demonstrated that 1, 25-(OH)2 -7-DHC interacts with LXRα residues in a manner distinct from potent agonists, such as T0901317 and 24( S ), 25-epoxycholesterol. 1α-OH-7-DHC and 1, 25-(OH)2 -7-DHC induced expression of LXR target genes in a cell type- and gene-selective manner. 1, 25-(OH)2 -7-DHC effectively suppressed lipopolysaccharide-stimulated proinflammatory gene expression in an LXR-dependent manner. Therefore, 1α-hydroxy derivatives, such as 1, 25-(OH)2 -7-DHC, are unique LXR modulators with selective agonistic activity and potent transrepression function. These oxysterols have potential as LXR-targeted therapeutics for inflammatory disease.